Learning mechanisms in pain chronification—teachings from placebo research. Issue 1 (April 2015) - Ingvar, Martin
Abstract : Abstract: This review presents a general model for the understanding of pain, placebo, and chronification of pain in the framework of cognitive neuroscience. The concept of a computational cost-function underlying the functional imaging responses to placebo manipulations is put forward and demonstrated to be compatible with the placebo literature including data that demonstrate that placebo responses as seen on the behavioural level may be elicited on all levels of the neuroaxis. In the same vein, chronification of pain is discussed as a consequence of brain mechanisms for learning and expectation. Further studies are necessary on the reversal of chronic pain given the weak effects of treatment but also due to alarming findings that suggest morphological changes in the brain pain regulatory systems concurrent with the chronification process. The burden of chronic pain is devastating both on the individual level and society level and affects more than one-quarter of the world's population. Women are greatly overrepresented in patients with chronic pain. Hence, both from a general standpoint and from reasons of health equity, it is of essence to advance research and care efforts. Success in these efforts will only be granted with better theoretical concepts of chronic pain mechanisms that maps into the framework of cognitive neuroscience.